Teacher CPD model integrating TPACK framework with attitude and character knowledge - Ariyana, Yoki; Komariah, Aan; Permana, Johar; Suryana, Asep (Universitas Jambi, Indonesia, 2025)
This study aimed to develop a comprehensive Teacher CPD (Continuous Professional Development) model integrating the TPACK framework with attitude and character knowledge. The model addressed both cognitive competencies, such as pedagogical, technological, and content knowledge, and non-cognitive competencies, including attitude and character traits. A mixed-methods approach was employed, combining quantitative data from a survey of 1,012 teachers across Indonesia with qualitative data from interviews. The findings reveal that teachers prioritize pedagogical, professional, social, and personality competencies, while also emphasizing the importance of attitude and character for effective teaching. Teachers with strong character traits, such as empathy, responsibility, and integrity, were found to be more effective in integrating technology and fostering positive classroom environments. The study highlights the need for CPD programs to focus on both technical skills and emotional intelligence, offering a more holistic approach to teacher development in the digital age.